Microparticle association and heterogeneity of tumor‐derived tissue factor in plasma: is it important for coagulation activation?. (February 2014) - Davila, M.; Robles‐Carrillo, L.; Unruh, D.; Huo, Q.; Gardiner, C.; Sargent, I. L.; Adam, M.; Woodhams, B. J.; Francis, J. L.; Bogdanov, V. Y.; Amirkhosravi, A.
Summary Background Tumor‐derived tissue factor (TF) activates coagulation in vitro and in vivo in an orthotopic model of human pancreatic cancer. Here, we further characterized tumor‐derived TF in this model. Methods Conditioned medium (CM) of L3.6pl human pancreatic tumor cells and plasma from nude mice bearing L3.6pl tumors were ultracentrifuged, and the pellets were filtered through membranes with different pore sizes. The size distribution of particles was analyzed in CM or plasma fractions with nanoparticle tracking and dynamic light scattering. Human TF antigen and activity were measured in pellets and supernatants with ELISA and clotting or thrombin generation assays, respectively. Human alternatively spliced TF (asTF) was measured with ELISA. Human TF and thrombin–antithrombin complex (TAT) concentrations were assessed in plasma of mice injected with filtered fractions of CM. Results Particles in both CM and plasma were < 0.4 μm. TF antigen and activity in the CM were mainly associated with microparticles (MP). Approximately 50% of antigen and 20% of activity were associated with particles of < 0.1 μm. Injection of < 0.1‐μm particles into mice caused a 30% drop in platelet counts and an increase in TAT levels. In contrast, 90% of TF antigen in tumor‐bearing mice plasmas was non‐sedimentable, whereas TF activity was exclusively associated with MP. Particles of < 0.1 μm and the supernatants of both CM and plasma gained TF activity after addition of exogenous phospholipids. Although asTF was found in MP‐free CM supernatants, it was also present in CM and plasma pellets. Conclusions Tumor‐derived particles of < 0.1 μm and non‐sedimentable TF are or can become procoagulant in the presence of phospholipids, and may contribute to the procoagulant potential of circulating TF.